Soil Characteristics and Quality Class of Sal (Shorea robusta) in West Dehra Dun Forest Division of U.P. - Samra, J. S.; Payal, P. S.; Sharma, S. D. (Indian Forester, 1985)
This investigation was undertake on Northern and Southern aspects of two ranges of hills separated by a narrow long valley. Sal (Shores robusta) is the predominant natural vegetation in the upper storey. Quality class of Sal ranged from 1.0 to 3.14 in Haplustalfs, 2.15 to 2.50 in Argiustolls and 1.86 to 2.30 in Haplustolls. Best quality class 1 of Sal was observed in Hapluatalfs on Northern aspect. However growth performance within a given level of taxa varied considerably mostly due to land and to some extent due to soil characteristics. In coarse loamy skeletal Udic Haplustolls and sandy skeletal Typic Udortha is, presence of gravels reduces the effective volume of soil which gets compensated to some extent due to deeder penetration of roots but quality is next to Udic Haplustalfs. From morphological characteristics and evidences of phytocycling of Ca and Mg it seems that interactions of natural vegetation and soil development very considerably in different soils. Haplustalfs on Northern aspect which receive more solar radiation and where growth of vegetation is better represent more developed soils as compared to Southern aspects.